2016
DOI: 10.1002/bdm.1949
|View full text |Cite
|
Sign up to set email alerts
|

Improving Accuracy on Bayesian Inference Problems Using a Brief Tutorial

Abstract: Research suggests that most people struggle when asked to interpret the outcomes of diagnostic tests such as those presented as Bayesian inference problems. To help people interpret these difficult problems, we created a brief tutorial, requiring less than 10 minutes, that guided participants through the creation of an aid (either graph or table) based on an example inference problem and then showed the correct way to calculate the positive predictive value of the problem (i.e., likelihood that positive tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 46 publications
1
45
1
Order By: Relevance
“…(2011), whereas area-proportionality did not prove to be a facilitating factor in Micallef et al. (2012) or Talboy and Schneider (2017).…”
Section: Research Questions and Hypotheses Concerning Visualizing Stamentioning
confidence: 90%
See 1 more Smart Citation
“…(2011), whereas area-proportionality did not prove to be a facilitating factor in Micallef et al. (2012) or Talboy and Schneider (2017).…”
Section: Research Questions and Hypotheses Concerning Visualizing Stamentioning
confidence: 90%
“…One idea about beneficial graphical properties of visualization refers to representing the statistical information area proportionally (e.g., Tsai et al., 2011; Micallef et al., 2012): “this accurate, proportional representation is considered a key feature of what makes a good visual aid” (Talboy and Schneider, 2017, p. 375). Theoretical arguments for area-proportional visualizations, such as the unit square (Figure 3B), are often formulated based on mathematical considerations: “Rectangular areas correspond to probabilities and can be used to calculate their numerical value and to determine the Bayes relation” (Oldford, 2003, p. 1).…”
Section: Research Questions and Hypotheses Concerning Visualizing Stamentioning
confidence: 99%
“…There is another strategy for improving Bayesian reasoning in the 1-test case, namely, visualizing the statistical information. Some prominent visualizations that have been developed are Euler diagrams (e.g., [ 29 31 ]), roulette-wheel diagrams (e.g., [ 32 , 33 ]), frequency grids (e.g., [ 23 , 34 , 35 ]), Eikosograms (sometimes also called unit squares or mosaic plots ; e.g., [ 36 39 ]), icon arrays (e.g., [ 32 , 40 , 41 ]), 2×2-tables (e.g., [ 14 , 42 ]), and tree diagrams (e.g., [ 14 , 33 , 42 44 ]). For an overview of these visualizations, see [ 14 ], and for corresponding visualizations regarding the 2-test case, see Fig 1 .…”
Section: The Medical 1-test Casementioning
confidence: 99%
“…Further, our results can be used to improve trainings of Bayesian reasoning that are based on a double-tree diagram (Wassner, 2004) or a unit square (Talboy and Schneider, 2017). When using a double-tree diagram, a specific focus must be put on identifying the correct subset H ∩ D, and emphasizing the related node as representing the intersection set H ∩ D that allows for the set inclusion (H ∩ D) ⊆ D. When using a unit square, our results imply that a specific focus must be put on identification of the correct basic set, since most of the students found a correct strategy based on this identification.…”
Section: Discussionmentioning
confidence: 99%
“…A unit square (Eichler and Vogel, 2015; Figure 3B) representing a nested style (Khan et al, 2015) was also found to facilitate Bayesian reasoning (Oldford, 2003;Eichler, 2017, 2019;Talboy and Schneider, 2017). In a unit square, the set inclusion (H ∩ D) ⊆ D and (H ∩ D) ⊆ D as well as (H ∩ D) ⊆ H and (H ∩D) ⊆ H are presented in one row or in one column.…”
Section: Visualization Of Bayesian Situationsmentioning
confidence: 99%